2002
DOI: 10.1046/j.1525-1594.2002.06847.x
|View full text |Cite
|
Sign up to set email alerts
|

An Infection‐Preventing Bilayered Collagen Membrane Containing Antibiotic‐Loaded Hyaluronan Microparticles: Physical and Biological Properties

Abstract: An infection-preventing bilayered membrane consisting of a dense and porous collagen membrane has been developed. The membrane was fabricated using a combined freeze-drying/air-drying method. Hyaluronan (HA) microparticles containing silver sulfadiazine (AgSD) were fabricated by gelling an HA solution with calcium chloride and were incorporated into collagen layers to allow the sustained release of AgSD. In vitro biodegradability of the membrane and the release of AgSD from the membrane could be controlled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…It might be because AgSD released from hydrogels of higher crosslinking level at a slower rate. Similar result had been reported by Lee et al, who found that cellular damage could be minimized by the sustained release of AgSD from collagen membrane [37]. The blank hydrogels displayed higher cell viability than negative control even at the highest crosslinking agent concentration, which was consistent with our previous report [22].…”
Section: Discussionsupporting
confidence: 92%
“…It might be because AgSD released from hydrogels of higher crosslinking level at a slower rate. Similar result had been reported by Lee et al, who found that cellular damage could be minimized by the sustained release of AgSD from collagen membrane [37]. The blank hydrogels displayed higher cell viability than negative control even at the highest crosslinking agent concentration, which was consistent with our previous report [22].…”
Section: Discussionsupporting
confidence: 92%
“…The observed pore size of few hundred mm wide and the interconnected character of the porosity of Ga-crosslinked alginate coated scaffolds indicate the suitability of the scaffolds for cell attachment, migration, and vascularization. [1,[4][5][6][7][8] Moreover, when the second coating of sodium alginate was applied, a rougher surface was obtained when compared with scaffolds with only one layer of sodium alginate coating [ Fig. 2(c) and (d)].…”
Section: Materials and Scaffold Characterizationmentioning
confidence: 99%
“…[4][5][6] These scaffolds should provide structural support for cells and the new tissue being formed, acting as a temporary extracellular matrix and inducing the progress of natural processes of tissue regeneration and development. [1,[6][7][8] Additionally, current research efforts also focus on the possibility of using the scaffold as a carrier for controlled drug release. [4,[9][10][11][12] In this context, there is a growing interest in exploring the possibility of using the scaffold itself to deliver therapeutic drugs to prevent possible bacterial colonization of the biomaterial following surgery, which would otherwise require administration of antibiotics systemically.…”
mentioning
confidence: 99%
“…To eradicate the biofilm, drug-releasing dressings should provide a long-term sustained release of drug. To this aim, a strategy consists in embedding drug-loaded microparticles in specific fibers or gels for wound dressing to be placed onto the wound bed in order to provide local and controlled drug release [38,39]. In this study, the kinetics of drug release from UA-loaded microparticles was investigated at different temperatures and the antimicrobial activity of the microparticles was assessed against a strain of S. epidermidis both in planktonic and in biofilm state.…”
Section: Introductionmentioning
confidence: 99%